Investigation of Tribological Properties of Metallic Materials with the Use of the Universal Friction Machine "MTU-1". (2017) - Perepelkina, S.; Kovalenko, P.; Pechenko, R.
Abstract: This paper deals with the main objectives of friction and wear tests, such as estimation of tribological characteristics of contacting surfaces, including friction coefficient, and selection of optimal combinations of materials and lubricants for particular purposes. In this paper, a methodology for estimation of friction coefficient with the use of the universal friction machine "MTU-1" has been considered. The method is based on the use of calibration graphs for adjustment of measurement parameters according to the characteristics of the surfaces and the environment.